An empirical analysis of capacity and flexibility planning under demand uncertainty. Issue 3 (3rd July 2021) - Hamidian, Nooshin; Sawhney, Rapinder; Pradhan, Ninad
ABSTRACT: This study explores the optimal capacity and production planning under stochastic demand accounting for price sensitivity and correlation impacts on demand. Four flexibility strategies in a multi-product setting considering resource flexibility along with at-capacity or below-capacity production are investigated. Each flexibility strategy is modeled as a two-stage stochastic programming problem to maximize the expected profit. In the first stage, the capacity of resources is determined. In the second stage, after demand realization, the production quantity of each product group considering the capacity limits defined in the first stage is specified. In this study, the significant role of demand correlation and price sensitivity in production and capacity planning and flexibility strategy selection is illustrated. Moreover, the impact of correlation, price-sensitivity, price, and demand variation on profit and flexibility strategy selection under different conditions are presented. We emphasize that selecting an appropriate flexibility strategy depends on cost factors as well, and the model should be solved accounting for each manufacturer's parameters such as investment cost, production cost, product correlation, and price.